P0933PROTECTIVE EFFECT OF AN SGLT2 INHIBITOR ON ER STRESS THROUGH REDUCTION OF ECTOPIC LIPID DEPOSITION IN RENAL TUBULES IN OBESE MICE. (6th June 2020) - Takata, Tomoaki; Hosokawa, Kohshiro; Sugihara, Takaaki; Matono, Tomomitsu; Koda, Masahiko; Kanda, Tsutomu; Ogawa, Masaya; Ida, Ayami; Mae, Yukari; Yamamoto, Marie; Iyama, Takuji; Fukuda, Satoko; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) is a major health issue closely related to metabolic syndrome. Although a potential link between ectopic lipid-induced ER stress and the progression of CKD has been suggested, the underlying mechanism has not yet been fully elucidated. SGLT2 inhibitors have been reported to be effective in reducing fat accumulation. However the effect on lipid-associated kidney disease remains unclear. The aim of this study was to investigate the role of ectopic lipid and ER stress in the development of CKD, and evaluate the efficacy of an SGLT2 inhibitor. Method: FLS-ob/ob mice, a model that shows significant ectopic lipid deposition and closely imitate the pathophysiology of non-alcoholic steatohepatitis, were treated with vehicle or an SGLT2 inhibitor, Ipragliflozin (1 mg/kg body weight) for 12 weeks. Metabolic characteristics, histology of the kidney, ER stress and apoptotic signals were evaluated. Results: Ipragliflozin significantly reduced the serum triglyceride level. Ectopic lipid deposition in renal tubules found in FLS-ob/ob mice was prevented by Ipragliflozin, accompanied by reduced interstitial fibrosis. Both GRP78, a master regulator or ER stress, and CHOP, a downstream mediator of ER stress, were significantly downregulated in mice treated with Ipragliflozin. Apoptotic signal in kidney tissue was also reduced. Conclusion: Ipragliflozin improved the pathogenesis of CKD by reducing ER stress through preventing ectopic lipid deposition in the kidney. SGLT2 inhibitors may have therapeutic effect on lipid-associated kidney disease.